PENANGANAN COVID 19 DITINJAU DARI SISI PERTAHANAN - ,, Andriani , (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
Covid-19 spreading is very fast. The outbreak of the Covid-19 virus has infected almost all countries in the world quickly around the world. The biggest threat to prevent the spread of corona virus is through asymptomatic people. With such rapid spread, it is very possible that Covid-19 threatens national defense. It is not enough for the government to just make this problem a health issue, but it is necessary to make it a national security threat. The community's economic background that is not too strong and health facilities that are still not very sophisticated can be the main reasons for the government as the number of cases increases. If Covid-19 cannot be resolved properly, it is easy, and it is very possible to develop in all aspects of national and other national life. In this case, all measures must be implemented by the government considering the increasingly critical situation. All strategies must be implemented both preventive and repressive. The preventive strategy that can be implemented is to impose regional quarantine, if there must be strict control over the community. In addition, there must also be socialization that is carried out in a more effective way to increase public awareness. The repressive steps that must be carried out are to immediately provide health facilities to build temporary hospitals with facilities and medical personnel that are truly adequate to deal with Covid-19.